The Influence of Islamic Leadership and The Performance of The Village Head on Village Economic Development Based on The Tauhidi Strenght Relation on Bengkalis District - Fadillah Al Mausuly; Yuswar Z .Basri; Zulheimy Zulheimy (Dinasti Publisher, 2023)
The village is a driving force for economic development and is a support for the progress of a country, so leaders in the village must be able to manage the economy and always improve village performance well so that development goals are achieved In Islamic teachings, progress in physical and material development is not the pinnacle of success, especially if it is achieved in an unfarly, endangering the state, nation and people, destroying nature, because it is basically detrimental and contrary to the rules of Allah SWT, does not bring true prosperity and happiness, thus how to integrate development that aims not only at physical and material growth that is visible but also at the forefront of Shari'a elements that are approved in accordance with Shari'ah demands This research was conducted in Bengkalis Regency. distributing questionnaires to 255 (two hundred and fifty five) respondents representing 11 sub-districts. Analysis of data processing in this study uses the Smart PLS 3.9.6 application to produce Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The path coefficient value (path coefficient) of Islamic Leadership on Village Economic Development in Bengkalis Regency is 0.278 with a calculated value of 3.659 and a p-value obtained of 0.000. If the t count > t table (1.975) or the p value <0.05 (significant level 5%), it can be concluded that leadership influences economic development, The path coefficient value of Village Government Performance on Village Economic Development in Bengkalis Regency is 0.178 with a calculated t value of 2.629 and a p value obtained of 0.009. If the t count > t table (1.975) or the p value <0.05 (significant level of 5%), it can be concluded that performance influences economic development.